Effects of Different Concentrations of Total Suspended Solids and Dissolved Oxygen on Survival and Growth of Juvenile Barbonymus schwanenfeldii and Oreochromis niloticus - Nona Nabilah, Binti Ahmad Tarmizi (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The purpose of this study is to determine the effects of different concentrations of total suspended solids (TSS) and dissolved oxygen (DO) on the survival rate and growth of a native species (Barbonymus schwanenfeldii) and an exotic species (Oreochromis niloticus). The two species of fish were placed in a tank with different concentrations of TSS; 0 mg/L, 500 mg/L, 1,000 mg/L, 5,000 mg/L, and 10,000 mg/L and different concentrations of DO; 7 mg/ L, 4 mg/L, 2 mg/L, 1 mg/L, and 0 mg/L. When both species were placed in different TSS concentrations, Barbonymus schwanenfeldii showed lower survival rate compared to Oreochromis niloticus at 10,000 mg/L of TSS. The FCR of Barbonymus schwanenfeldii was significantly higher than Oreochromis niloticus in all of the treatments. When both species were tested at the five DO concentrations, Barbonymus schwanenfeldii showed lower survival rate compared to Oreochromis niloticus. Both fish recorded the highest survival rate at 7 mg/L of DO. There is no survival for both species at 2 mg/L, 1 mg/L and 0 mg/L. The FCR of Barbonymus schwanenfeldii was significantly higher than Oreochromis niloticus at 7 mg/L and 4 mg/L. These conclude that Oreochromis niloticus (exotic species) is hardier than Barbonymus schwanenfeldii (native species). The outcome of this study could be used to determine the effects of changes in habitat on the overall population of Barbonymus schwanenfeldii and Oreochromis niloticus.